Promotion of cactus pear as a multipurpose crop to enhance the livelihood of poor farmers in dry areas of Northern Africa and Western Asia - CGIAR Research Program on Livestock (2020)
ICARDA developed a suite of best-bet agronomic practices to maximize productivity. To change farmers’ attitudes and practices regarding cactus pear, ICARDA carried out awareness-raising and capacity development. We trained farmers on using cactus pear as fodder reserve. We facilitated business development by sharing experiences about all aspects of cactus use.